Huge lipomatous tumor in the adductor muscle - Zonnur, S.; Falkeis, C.; Ondang, G.; Weiner, M.; Maier, H.; Agaimy, Abbas (Pathologe, 2015)
Deep-seated lipomatous tumors of the peripheral soft tissue of the extremities are uncommon. The majority represent atypical lipomatous tumors or well-differentiated liposarcomas. On rare occasions benign adipocytic tumors, such as hibernoma may present as huge, deep-lying subfascial masses. As a consequence of the deep location and usually heterogeneous signal intensities in imaging, they are particularly at risk to be misinterpreted as liposarcomas on clinical grounds. Furthermore, the rarity and thus limited familiarity with the morphological appearance and spectrum still represent a pitfall for the histopathological assessment.
EVALuna2:6720